A spatial multi-criteria model for the evaluation of land redistribution plans - Demetriou, Demetris; See, Linda; Stillwell, John (My University, 2012)
A planning support system for land consolidation has been developed that has, at its heart, an expert system called LandSpaCES (Land Spatial Consolidation Expert System) which contains a "design module" that generates alternative land redistributions under different scenarios and an "evaluation module" which integrates GIS with multi-criteria decision making for assessing these alternatives. This paper introduces the structural framework of the latter module which has been applied using a case study in Cyprus. Two new indices are introduced: the "parcel concentration coefficient" for measuring the dispersion of parcels; and the "landowner satisfaction rate" for predicting the acceptance of the land redistribution plan by the landowners in terms of the location of their new parcels. These two indices are used as criteria for the evaluation of the land redistribution alternatives and are transferable to any land consolidation project. Moreover, a modified version of the ratio estimation procedure, referred to as the "qualitative rating method" for assigning weights to the evaluation criteria, is presented, along with a set of non-linear value functions for standardizing the performance scores of the alternatives and incorporating expert knowledge for five evaluation criteria. The application of the module showed that it is a powerful new tool for the evaluation of alternative land redistribution plans that could be implemented in other countries after appropriate adjustments. A broader contribution has also been made to spatial planning processes, which might follow the methodology and innovations presented in this paper.
Keywords: GIS; Land consolidation; Landowner satisfaction rate; Multi-attribute decision making; Parcel concentration coefficient; Qualitative rating method; Value functions